Structural Drivers of Vulnerability at the Human-Rodent Interface in the Limpopo National Park, Mozambique - Muriel Figuié; Lourenço Mapaco; Alexandre Caron; Leonardo Hofisso; Iara Gomes-Jaintilal; Julien Cappelle (CABI, 2023)
Abstract This socio-anthropological study investigates the relations between humans and rodents in an area adjacent to the Limpopo National Park in Mozambique. Designed as part of the larger researcher on mammarenaviruses, it explores the social dimensions of the rodent-human interface, considering its spatial and temporal variability. Its results contribute to our understanding of the socio-ecological context in which new pathogens or new routes of pathogen transmission could arise and potentially spread diseases. A vulnerability-based approach was used to assess human exposure, sensibility and capacity to adapt to rodents. This study revealed: (i) Local knowledge of the dynamic of rodent populations over the last few decades, with new invasive rodents displacing native species; (ii) the social-ecological factors thought to be behind this invasion: climate change, new infrastructure (e.g., construction of a dam), new agricultural practices (e.g., cultivation of sunflowers) and policies (human resettlement); (iii) the significant impact associated with new invasive rodents (e.g., crop losses, damage to belongings), the limited capacity for individual and collective interventions to mitigate damage, and the little concern shown for rodent-related diseases; (iv) women and girls' high vulnerability to potential rodent-borne diseases due to frequent direct and indirect contact with rodents in the domestic space; and (v) the added-value of using a vulnerability-based methodology, over the more commonly used Knowledge-Attitudes-Practices (KAP) methodology, to map the structural factors shaping the human-rodent interface and its dynamic. Our findings suggest that the vulnerability-based approach could offer an opportunity to better respond to the One Health ambition by integrating social dimensions of health and grasping the complexity of the social and material context in which new pathogens could emerge and spread. One Health Statement The present socio-anthropological study of the human-rodent interface comes in complement to a previous eco-epidemiological survey focusing on the rodent-virus interface. It explores the cultural and social dimensions of the interactions between rodent-human, considering spatial and temporal variability. In doing so, it contributes to the understanding of the socio-ecological dynamic, in which new viral transmission can occur and disease spread. It exemplifies, based on local knowledge, how socio-ecological changes can create new routes for the emerging virus and highlights the vulnerability of the exposed human population to address the potential related health risks. This multidisciplinary and dynamic approach of how humans and rodents interact, and how these interactions are shaped by their changing environment is a contribution to a systemic approach to health, in line with the One health paradigm.